2016
DOI: 10.1161/circulationaha.115.016697
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Myocardial Repolarization Reserve in Adolescent Females With Anorexia Nervosa

Abstract: Background-Patients with anorexia nervosa exhibit abnormal myocardial repolarization and are susceptible to sudden cardiac death. Exercise testing is useful in unmasking QT prolongation in disorders associated with abnormal repolarization. We characterized QT adaptation during exercise in anorexia. Methods and Results-Sixty-one adolescent female patients with anorexia nervosa and 45 age-and sex-matched healthy volunteers performed symptom-limited cycle ergometry during 12-lead ECG monitoring. Changes in the QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The QTc is the measure of the time between the start of the Q wave and the end of the T wave on the patient's electrocardiogram, corrected for heart rate, which represents the electrical depolarization and repolarization of the ventricles of the heart (Postema & Wilde, ). A lengthened QTc interval may be associated with increased risk for a ventricular arrhythmia and sudden death (Padfield et al, ; Postema & Wilde, ). Previous studies in non‐ED populations demonstrated lengthening (Meher, Bhattacharjee, Rampal, Kapoor, & Sharma, ), shortening (Chinushi et al, ; Srinath & Ravipati, ), or mixed results (Berger et al, ) of the QTc postexercise.…”
Section: Introductionmentioning
confidence: 99%
“…The QTc is the measure of the time between the start of the Q wave and the end of the T wave on the patient's electrocardiogram, corrected for heart rate, which represents the electrical depolarization and repolarization of the ventricles of the heart (Postema & Wilde, ). A lengthened QTc interval may be associated with increased risk for a ventricular arrhythmia and sudden death (Padfield et al, ; Postema & Wilde, ). Previous studies in non‐ED populations demonstrated lengthening (Meher, Bhattacharjee, Rampal, Kapoor, & Sharma, ), shortening (Chinushi et al, ; Srinath & Ravipati, ), or mixed results (Berger et al, ) of the QTc postexercise.…”
Section: Introductionmentioning
confidence: 99%
“…We thank Aparci et al for their interest in our article 1 and for the interesting points they raise. We agree that the pathogenesis of ventricular arrhythmias in anorexia nervosa (AN) is likely to be multifactorial; however, the argument that excess growth hormone (GH) may be responsible for arrhythmogenesis in AN is not particularly convincing.…”
Section: In Responsementioning
confidence: 87%
“…The main cardiovascular complications in patients with AN are bradycardia, systolic dysfunction, impaired ventricular repolarization, low blood pressure, QT interval prolongation, mitral valve prolapse, and reduction of myocardial contractility [1, 2]. The mechanistic pathways linking AN to left ventricular systolic function decline are not clear.…”
Section: Discussionmentioning
confidence: 99%